Analisis Variabel Fundamental dan Variabel Makroekonomi dalam Memprediksi Financial Distress - Solecha, Yeni; Yeni Kuntari; Elma Muncar Aditya (Jurnal Ilmiah Aset, 2025)
This study aims to determine the effect of ROA, CR, DER, TATO, Interest Rate, Inflation, and Exchange Rate on Financial Distress. The population in this study were state-owned enterprises listed on the Indonesia Stock Exchange in 2020-2023. The sampling method used in this study was a purposive sampling method and obtained a sample of 20 companies. The data used in this study were obtained from the annual financial reports of state-owned enterprises listed on the Indonesia Stock Exchange in 2020-2023. The data analysis method in this study was Multiple Linear Regression analysis. The results showed that simultaneously the variables ROA, CR, DER, TATO, Interest Rate, Inflation, and Exchange Rate had a significant effect on Financial Distress, partially ROA and TATO had a significant effect on Financial Distress, while CR, DER, Interest Rate, Inflation, and Exchange Rate had no effect on Financial Distress.